Educational Chain Whisper Game for Improving Listening and Memory Based on Local Wisdom - Ahsanurrijal Ahsanurrijal; Fadly Akbar; Ahmad Ahmad; Ahmad Rizal Abdullah; Aswadi Ramli (PT. Global Research Collaboration, 2025)
This community service is focused on improving students' listening and memory skills through the implementation of an educational